Analisis Propagasi Jaringan Komunikasi Radio VHF di PT. Julian Adiputra Utama - Achmad Fikri Gustiyanda Gustiyanda; Aan Restu Mukti (Universitas Muhammadiyah Riau, 2022)
PT. Julian Adiputra Utama is a private company engaged in telecommunications and information. PT. Julian Adiputra Utama is a private company engaged in telecommunications and information. Based on the author's observations about PT. Julian Adiputra Utama has a radio tower to support activities and control office activities and optimize company performance. Weather conditions when using VHF radio frequency signals are very influential and the electricity users in the tower must be adequate. The problems faced when communicating are the loss of a signal on one of the communication tools with technology such as the VHF radio communication network, the problems faced. The frequency signal will be sent to a device, namely a repeater aimed at retransmitting the frequency signal that was emitted at the beginning of 2 km to 30 km. Based on the author's observations of PT. Julian Adiputra Utama has a radio tower to support office activities and control activities and optimize company performance. Weather conditions when using RF VHF signals are very influential, and power users in towers must be adequate. The problem faced when communicating is the loss of signal in one of the means of communication that uses technology such as VHF radio communication networks.